Memórias de escolarização na perspectiva da escola étnica paroquial em Kronenthal/ Vale Real - RS (1933-1965) - Mello, Mariane Fruet de (My University, 2020)
This work, linked to the Graduate Program in Education at the University of Caxias do Sul, and entitled “Memories of Schooling from the perspective of the Parochial Ethnic School in Kronenthal / Vale Real - RS (1933-1965)” has a historical character with a focus on education practices in the locality after the establishment of its first school. Here, then, the following question is answered: "How were the schooling processes of Kronenthal / Vale Real - RS constituted through the Étnica Paroquial School, and what were the educational practices like at that School?". The general objective of the investigation is to analyze the memories of schooling in the municipality, through interviews with former students of the researched institution, establishing relationships with the historical context and the different social groups that settled in the village. In order to comply with the proposal, we specifically sought to: identify and understand the relationships between the community and the mobilization of residents for the institution of the parochial ethnic school in the municipality, as well as establishing relationships with the historical context of that period; identify, understand and establish possible relations between the institutionalization of the Kronenthal Parochial Ethnic School, its form of organization, and its school culture. The qualitative investigation used the Oral History methodology; the analysis was also applied to personal documents, such as photographs, teacher's school transcript, notebook, certificate and safe conduct, accessed through the personal collection of the interviewees and other collaborators. The research is based on the theoretical and methodological assumptions of Cultural History, from the dialogue with historians such as Burke (1992; 2008), Chartier (1990), Le Goff (1990) and Pesavento (2005). To make the theoretical structure viable, the concepts of Ethnic School, proposed by Kreutz (1991), Rambo (1994), Luchese (2010), of memory, from Le Goff (1996), Bosi (2004) and Halbwachs, are also used (2006), and school cultures, by Vidal (2005) and Julia (2001).The dissertation is organized in five chapters, the first of initial considerations, which contextualizes the study, the second of introducing the methodological path of Oral History and documentary analysis, the third of delimiting the educational field and discussing the immigration process until the arrival of immigrants in the locality of Kronenthal - in the 19th century, the fourth chapter of the history of the Parish School of Kronenthal / Vale Real RS, through the narratives of the interviewees' memories, and the fifth of final considerations. This work was able to reproduce, with narratives and documents, a history of schooling in the locality, based on the memories of the Parochial School, on the analysis of its influences in society and by the Church and in the reconstruction of the role of the teacher and the classes. As a result, it was possible to show that the research allowed access to very particular views, according to each narrative of the interviewees who, although subjective, found correspondence in the group and were then able to give life to the school not portrayed by official documents and forgotten by the local community. The use of purely official sources would generate a colder discussion, perhaps distant even if objective, without a wealth of details generated by feelings and words that, after all, always built history.
Este trabalho, vinculado ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, e intitulado “Memórias de Escolarização na perspectiva da Escola Étnica Paroquial em Kronenthal/Vale Real – RS (1933-1965)” possui caráter histórico com enfoque nas práticas de educação da localidade a partir da constituição de sua primeira escola. Responde-se, aqui, então, ao seguinte questionamento: “Como se constituíram os processos de escolarização de Kronenthal/Vale Real – RS por meio da Escola Étnica Paroquial, e como eram as práticas educativas nessa Escola?”. O objetivo geral da investigação é analisar as memórias de escolarização no município, por meio de entrevistas com ex-alunos da instituição pesquisada, estabelecendo relações com o contexto histórico e os distintos grupos sociais que se fixaram no povoado. Para cumprir com o proposto, buscou-se, especificamente: identificar e compreender as relações entre a comunidade e a mobilização dos moradores para a instituição da Escola étnica paroquial no município, bem como estabelecer relações com o contexto histórico daquele período; identificar, compreender e estabelecer possíveis relações entre a institucionalização da Escola Étnica Paroquial de Kronenthal, sua forma de organização, e sua cultura escolar. A investigação de caráter qualitativo utilizou da metodologia da História Oral; a análise foi também aplicada a documentos pessoais, como fotografias, históric*-o escolar de professor, caderno, certificado e salvo conduto, acessados por meio de acervo pessoal dos entrevistados e de outros colaboradores. A pesquisa fundamenta-se nos pressupostos teórico-metodológicos da História Cultural, a partir do diálogo com historiadores como Burke (1992; 2008), Chartier (1990), Le Goff (1990) e Pesavento (2005). Para viabilizar a estrutura teórica, também são utilizados os conceitos de Escola Étnica, propostos por Kreutz (1991), Rambo (1994), Luchese (2010), de memória, a partir de Le Goff (1996), Bosi (2004) e Halbwachs (2006), e de culturas escolares, por Vidal (2005) e Julia (2001). A dissertação está organizada em cinco capítulos, sendo o primeiro de considerações iniciais, que contextualiza o estudo, o segundo de introdução do percurso metodológico da História Oral e análise documental, o terceiro de delimitação do campo educacional e de discussão do processo de imigração até a chegada dos imigrantes na localidade de Kronenthal – no século XIX, o quarto capítulo de apresentação da história da Escola Paroquial de Kronenthal/Vale Real RS, por meio das narrativas das memórias dos entrevistados, e o quinto de considerações finais. Este trabalho pôde reproduzir, com narrativas e documentos, uma história da escolarização da localidade, baseada nas memórias da Escola Paroquial, na análise de suas influências na sociedade e pela Igreja e na reconstrução do papel do professor e das aulas. Como resultados foi possível evidenciar que a pesquisa permitiu acessar visões bem particulares, de acordo com cada narrativa dos entrevistados que, apesar de subjetivas, encontraram correspondência no grupo e puderam, então, dar vida à escola não retratada pelos documentos oficiais e esquecida pela comunidade local. A utilização de fontes meramente oficiais geraria uma discussão mais fria, talvez distante ainda que objetiva, sem riqueza de detalhes gerada por sentimentos e pelas palavras que afinal sempre construíram a história
Keywords: Educação - História; Memória; Antropologia educacional; Education - History; Memory; Educational anthropology